Auditor's Success in Detecting Fraud: The Role of Professional Ethics and Workload - Astuti, Wati Aris; Sanggrahwati, Melly (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2023)
The purpose of this study is to assess the impact of workload and professional ethics on an auditor's capacity to spot fraud in 12 public accounting firms located in Bandung that are listed on the Indonesia Stock Exchange (IDX). Descriptive and verification study of forty auditors from twelve public accounting firms in Bandung that are listed on the Indonesia Stock Exchange (IDX) is the methodology employed.. Using a questionnaire, the survey approach was used to gather the majority of the data. Following data collection, SPSS 23.0 0 software was used to do multiple linear regression analysis on the data. The findings demonstrated that while workload had a negative and substantial impact on the auditor's ability to detect fraud, professional ethics had a positive and significant impact.